Analisis hubungan literasi kesehatan ibu dengan perkembangan Balita - Putri, Anggie Pradana; Iswahyuni, Sri; Rejo, Rejo; AM, Ady Irawan (Journal of Language and Health, 2025)
Latar Belakang: Periode usia nol sampai lima tahun merupakan masa emas perkembangan anak yang menentukan fondasi kognitif, motorik, bahasa, dan sosial-emosional. Literasi kesehatan ibu berperan penting dalam mendukung praktik pengasuhan yang optimal pada masa ini. Tujuan: Penelitian ini bertujuan untuk menganalisis hubungan antara tingkat literasi kesehatan ibu dan perkembangan balita. Metode: Penelitian ini menggunakan desain cross-sectional dengan melibatkan 187 pasangan ibu-anak usia 0–59 bulan di wilayah kerja Puskesmas Sukoharjo. Literasi kesehatan ibu diukur menggunakan HLS-EU-SF12-Indonesia, sedangkan perkembangan anak dinilai melalui Kuesioner Pra Skrining Perkembangan (KPSP). Data dianalisis menggunakan uji Chi-Square. Hasil: Mayoritas ibu memiliki literasi kesehatan kategori inadequate (37,4%) dan problematic (34,8%). Sebanyak 35,8% balita menunjukkan perkembangan yang meragukan atau menyimpang. Hasil uji Chi-Square menunjukkan hubungan yang signifikan antara literasi kesehatan ibu dan perkembangan balita (χ² = 21,84; p = 0,000), di mana tingkat literasi yang lebih baik berkorelasi dengan proporsi perkembangan anak yang lebih sesuai. Kesimpulan: Literasi kesehatan ibu berhubungan signifikan dengan perkembangan balita. Peningkatan literasi kesehatan ibu melalui intervensi edukatif yang kontekstual sangat penting untuk mendukung pengasuhan dan tumbuh kembang anak secara optimal. Background: The early childhood period zero to five years is known as the golden age, which plays a vital role in shaping children’s cognitive, motor, language, and socio-emotional development. Mothers, as primary caregivers, have a significant influence on child development, especially through their level of health literacy. Maternal health literacy, defined as the ability to obtain, understand, assess, and apply health information, has been shown to affect parenting quality and the developmental outcomes of children. Objective: This study aimed to analyze the relationship between maternal health literacy and child development among mothers with children aged 0–59 months in the working area of Sukoharjo Public Health Center, Indonesia. Methods: A cross-sectional quantitative approach was employed with 187 mother–child pairs selected using stratified random sampling. Maternal health literacy was measured using the HLS-EU-SF12-Indonesia instrument, while child development was assessed with the Pre-Screening Developmental Questionnaire (KPSP). Data were analyzed using descriptive statistics and Chi-Square tests with SPSS 22.0. Results: The majority of mothers had low to problematic levels of health literacy (inadequate: 37.4%, problematic: 34.8%), while only 9.1% had excellent literacy. Meanwhile, 35.8% of children were found to have questionable or delayed development. A significant relationship was found between maternal health literacy and child developmental status (χ² = 21.84; df = 3; p < 0.001), with higher literacy levels associated with a greater proportion of children achieving age-appropriate developmental milestones. Conclusion: Maternal health literacy is significantly associated with child development. Mothers with higher literacy levels are more likely to provide optimal caregiving and stimulation, leading to better developmental outcomes in their children. Strengthening maternal health literacy should become a strategic component in public health interventions to support early childhood development.